Introduction to philanthropy in education: diverse perspectives and global trends (2019)
In recent years, the changing landscape of philanthropic actors engaging in the development sector and the call for their active involvement in achieving the Sustainable Development Goals have prompted renewed discussions on the role of philanthropy. The topic has gained prominence in the education community at large, but also within international cooperation and development agencies. Philanthropy is being called upon to solve some of the world’s most complex social development challenges (see Cohen, 2014; Dean, 2013). This has included initiatives by prominent philanthropists, such as the Giving Pledge that was launched by Warren Buffet and Bill Gates in 2010, to secure commitments from billionaires to give at least half of their wealth to charity. By 2019, 188 billionaires in 22 countries (The Giving Pledge, n.d.) had signed the pledge which could amount to USD 600 billion by the year 2020 (Kotecki, 2018). Given the substantial gap in government and donor funds for education reform in developing countries, many actors in the education community have made the case for finding a philanthropist champion, like Bill Gates, to catalyse discussions and mobilise substantial investments for global education (Brown, 2012; The Global Partnership for Education, 2017; Haslebacher & van Fleet, 2011). Yet, the role of philanthropies in education reform, especially in developing countries, is severely understudied.